PRIMARY SCHOOL - THE FOUNDATION OF SUCCESSFUL PERSONALITY DEVELOPMENT - Meshcheryakova, T.V. (Pedagogy of Higher and Secondary Education, 2022)
The article analyzes the work of teachers Saksagansky, October and Central City Districts of Kryvyi Rih on solving the problem of development of gifted junior schoolchildren.